DIABETES MELLITUS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Diabetes mellitus is a disease caused by insulin deficiency and metabolic disorders in the body. Diabetes has been known for a very long time in the history of eastern folk medicine. Abu Ali ibn Sina pays special attention to this pain. "Water comes out the way it was drunk," he wrote. If the patient drinks a lot of water, it will cause other diseases and the patient will lose a lot of weight. Stopping the treatment, the doctor says: "Give the patient cold fluids, put them in a cooler, drink sour yogurt, give them fruits, drink mint, that is, wet the patient and cool him." This means that the disease occurs due to excess heat in the human body